Analisis Faktor-Faktor Penentu Volatilitas Harga Saham Perusahan Sub Sektor Minyak, Gas dan Batu Bara Yang Terdaftar Di BEI - Nurlida Hairin Nafisa; Alwi; Nurhayati (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
Departing from the global phenomena of the last five years which are suspected to have caused the movement of global investment trends in companies in the oil, gas and coal sub-sector companies and as many as 29 oil, gas and coal sub-sector stocks listed on the IDX are listed by the IDX as stocks in the UMA (Unusual Market Activity) category for the 2021 – 2023 period. The researcher conducted the study with the aim of analyzing the influence of Asset Growth, Earning Volatility, Leverage, and Firm Size on Stock Price Volatility. The results of this study prove that the variables Asset Growth, Earning volatility, Leverage and Firm Size do not have a significant effect partially or simultaneously on the Stock Price Volatility of companies in the oil, gas and coal sub-sector listed on the IDX for the period 2019 – 2024. This research can be useful for companies and investors to know that stock price volatility is not only influenced by internal factors. So that investors can more closely monitor investment risks based on global phenomena or political news that occurs. This study is an associative quantitative research using data analysis techniques of classical assumption test, multiple linear regression test, correlation coefficient test, determination coefficient test, F test (simultaneous) and T test (partial). Keywords: Asset_Growth, Earning_Volatility, Leverage, Firm_Size and Stock_Price_ Volatility